Alginate Encapsulation of Begonia Microshoots for Short-Term Storage and Distribution - Hamidou F. Sakhanokho; Cecil T. Pounders; Eugene K. Blythe (The Scientific World Journal)
Synthetic seeds were formed from shoot tips of two in vitro grown Begonia cultivars using 3% sodium alginate in Murashige and Skoog medium (MS) salt solution as the gel matrix and 100 mM calcium chloride for complexation. Synthetic seed formation was achieved by releasing the sodium alginate/explant combination into 100 mM calcium chloride (CaCl2·H2O) solution for 30 or 45 min. Both control and encapsulated shoots were transferred into sterile Petri dishes and stored at 4°C or 22°C for 0, 2, 4, 6, or 8 weeks. Conversion of synthetic seeds into plantlets for both storage environments was assessed in MS medium or peat-based substrate. No significant difference was found between the 30 and 45 min CaCl2·H2O treatments or the two cultivars. Encapsulation of explants improved survival rate over time irrespective of the medium type or storage environment. Survival rates of 88, 53, 28, and 11% for encapsulated microshoots versus 73, 13, 0, and 0% for control explants were achieved in microshoots stored for 2, 4, 6, and 8 weeks, respectively. The best results were obtained when synthetic seeds were stored at 4°C and germinated on MS medium. Regenerated plantlets were successfully established in potting soil.